Avaliação da eficiência de mercado para o setor privado brasileiro de educação: estudo de evento - Corrêa, Érica Posch de Carvalho (2013)
This study aims at evaluating the hypothesis of market efficiency for the private education sector in Brazil. This analysis is based on an evaluation of the return that stocks have over the disclosures of material facts and quarterly results, using the hypothesis of semi-strong informational efficiency of the market, developed by Fama (1970). From historical data of stock prices of four companies listed on the Bovespa Index, it is possible to assess whether this market meets the specific market efficiency requirements of the theory, or on the other hand, it has inefficiencies that market players could use to obtain abnormal returns. We evaluated acquisitions and releases of quarterly results, in order to have an overview of corporate information. The conclusion is that one cannot reject the efficient market hypothesis, as the market reacted to new information published, and the reaction was absorbed by the price of assets, after the event window